2017
DOI: 10.1136/thoraxjnl-2017-210226
|View full text |Cite
|
Sign up to set email alerts
|

Metal worker’s lung: spatial association with Mycobacterium avium

Abstract: BackgroundOutbreaks of hypersensitivity pneumonitis (HP) are not uncommon in workplaces where metal working fluid (MWF) is used to facilitate metal turning. Inhalation of microbe-contaminated MWF has been assumed to be the cause, but previous investigations have failed to establish a spatial relationship between a contaminated source and an outbreak.ObjectivesAfter an outbreak of five cases of HP in a UK factory, we carried out blinded, molecular-based microbiological investigation of MWF samples in order to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…This is entirely in keeping with data from the UK reporting scheme for occupational HP between 1996 and 2015, where exposure to MWF (35% of cases) and farming (17% of cases) were the most common causes 27. The reporting data demonstrated that over this time period, ‘Metalworking fluid HP’ has become the most commonly reported cause of occupational HP in the UK, a change in epidemiology that merits further research 28…”
Section: Discussionsupporting
confidence: 77%
“…This is entirely in keeping with data from the UK reporting scheme for occupational HP between 1996 and 2015, where exposure to MWF (35% of cases) and farming (17% of cases) were the most common causes 27. The reporting data demonstrated that over this time period, ‘Metalworking fluid HP’ has become the most commonly reported cause of occupational HP in the UK, a change in epidemiology that merits further research 28…”
Section: Discussionsupporting
confidence: 77%
“…Barber et al [11] revealed that MWF has replaced farmers' lung as the commonest cause of occupational HP from the UK SWORD surveillance scheme for work-related respiratory disease; there is co-linearity with our cases, as these would also have been reported to SWORD. MWF-related HP is often precipitated by pooling and re-circulation of used MWF via common sumps, the exact cause usually remaining elusive; mycobacterial species have been implicated in some outbreaks [17,18] although evidence for cause and effect is lacking. Regulations in the UK [19] require employers, who undertake processes that use MWF and expose their workforce by inhalation, ingestion or skin contact, to put prevention-or control measures in place.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach of identifying the irregularities of the lung specimen through ultramicroscopy provides unique evidence of the adverse effects of heavy metals on lung cells (Sporn and Roggli, 2016). A recent report described an outbreak of metalworking fluid (MWF)-associated hypersensitivity pneumonitis caused by mycobacterium-like organisms among some metal workers (James et al, 2018). Although workers working with MWF are in a different category than those which we studied, such findings also can be explained in the context of an altered spectrum of immune cells in the lungs due to occupational exposure, such as that we found in our study on welders.…”
Section: Discussionmentioning
confidence: 99%